Revealing PTSD Symptoms Experienced by Kat Baker Using Internal Conflicts in “Spinning Out” TV Series - Putri, Putu Agnatya Mahadi; Aryawibawa, I Nyoman; Sudipa, I Nengah (Stilistika : Journal of Indonesian Language and Literature, 2023)
This article presents a qualitative psychoanalysis study on the main character named Kat baker in TV Series titled "Spinning Out". The main character of this series is vividly clear to correlate with PTSD symptoms, which makes it very interesting to analyze the internal conflict that experienced by Kat baker. Therefore, following article analyze Kat Baker’s PTSD symptoms with Internal conflict theory and identify the cause of Kat Baker’s PTSD in the Spinning Out TV series. The methodology applied was descriptive qualitative where the writer analyzed the non-numerical data from Spinning Out TV series in video form. The results of this study reveals two Interpersonal conflict identification that reveals Intrusion, Avoidance, Negative Alterations in Cognitions and Mood, and Arousal and Reactivity PTSD symptoms. Kat baker’s PTSD symptoms can be explained with internal conflict theory that considers the character's mental state and her battle to overcome her trauma.